The FNIP co-chaperones decelerate the Hsp90 chaperone cycle and enhance drug binding - Mark R. Woodford (Nature Portfolio, 2016)
Hsp90 is required for the folding, stability and activity of several drivers of oncogenesis. Here the authors show that Folliculin-interacting proteins (FNIP) 1 and 2, whose expression correlates with the cellular response to Hsp90 inhibitors, are co-chaperones of Hsp90 that function by inhibiting its ATPase activity.